Bioavailability and therapeutic activity of alicaforsen (ISIS 2302) administered as a rectal retention enema to subjects with active ulcerative colitis - MINER, P. B.; GEARY, R. S.; MATSON, J.; CHUANG, E.; XIA, S.; BAKER, B. F.; WEDEL, M. K. (Alimentary pharmacology & therapeutics, 2006)
Summary Background Alicaforsen is a phosphorothioate‐modified antisense oligodeoxynucleotide designed to sequence‐specifically reduce intercellular adhesion molecule 1 messenger RNA levels. Aims To determine the systemic and local bioavailability of alicaforsen, and its activity when administered as a once daily enema in subjects with active ulcerative colitis. Methods An open‐label study was conducted to assess the relative absorption (local and systemic pharmacokinetics) and pharmacologic activity of alicaforsen enema in subjects with active ulcerative colitis. Fifteen subjects received nightly enemas of alicaforsen (240 mg) for a treatment period of 6 weeks. Alicaforsen concentrations in plasma and colonic tissue biopsies were determined. Disease activity index and multiple measurements including endoscopy were used to assess alicaforsen activity in these subjects. Results Plasma concentrations of parent alicaforsen represented < 0.6% mean bioavailability when compared with historical intravenous area under the plasma concentration–time curves. Concentrations of the intact oligonucleotide in mucosal colonic tissue biopsies were orders of magnitude higher than those observed in plasma. A 46% reduction in mean Disease Activity Index and 33% rate of remission as defined by complete mucosal healing were observed at the end of treatment. Conclusion These data confirm that alicaforsen enema provides local treatment for a local disease with little meaningful systemic exposure.